2015
DOI: 10.17759/psylaw.2015050412
|View full text |Cite
|
Sign up to set email alerts
|

Running head: Relative judgment. When the relative judgment theory proved to be false

Abstract: A commonly accepted theory is that when witnesses can identify culprits in lineups, they will concentrate on him. On the other hand, when they cannot they compare between lineup members and choose the person most similar to the culprit. Therefore they will divide their gaze more equally between foils. An eye tracker was used with a 48-person lineup (four screens with twelve photos in each) in an attempt to demonstrate the superiority of gaze behavior over the verbal response. Surprisingly witnesses usually con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The result has been a dramatic reduction in mistaken identifications at no cost to correct ones. For example, with a typical rate of 50% mistaken choices in the traditional six- Levi has conducted a number of experiments using a twominute video as the eyewitness event, and a 48-person lineup Levi [14][15][16][17][18][19][20], Levi & Menashe [21]. The rate of identifications of the target in target-present lineups was usually about 33%.…”
Section: This Remains Too Large a Large Danger For An Innocent Suspectmentioning
confidence: 99%
“…The result has been a dramatic reduction in mistaken identifications at no cost to correct ones. For example, with a typical rate of 50% mistaken choices in the traditional six- Levi has conducted a number of experiments using a twominute video as the eyewitness event, and a 48-person lineup Levi [14][15][16][17][18][19][20], Levi & Menashe [21]. The rate of identifications of the target in target-present lineups was usually about 33%.…”
Section: This Remains Too Large a Large Danger For An Innocent Suspectmentioning
confidence: 99%
“…If this is true we will be able to dispense with the unreliable verbal response of the witness and base identification decisions on their gaze pattern instead, increasing correct identifications and decreasing mistaken ones. This next experiment [20] used a 48 person line-up, rather than a 6 person simultaneous one, since the interest is increasing identifications in large line-ups.…”
Section: Short Communicationmentioning
confidence: 99%
“…This is clearly a tremendous improvement. Early research seems to have discouraged exploring this approach [14][15][16]. However, this research showed only one photo at a time.…”
Section: Introductionmentioning
confidence: 95%